Perilaku Sosial Keagamaan Gen Z Di Era Digital Di Desa Talang Padang Kecamatan Pino Raya Kabupaten Bengkulu Selatan - Reza Oktavia Reza Oktavia; Nova Ananda; Tanti Marni; Samsudin; Saepudin; Rossi Delta Fitriana (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
This study aims to: (1) describe the behavioral characteristics of Generation Z in the digital era in Talang Padang Village, Pino Raya District, South Bengkulu Regency; and (2) analyze the socio-religious behavior of Generation Z in the village. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, interviews, and documentation with informants from Generation Z, community leaders, and religious leaders. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of the study show that the characteristics of Generation Z in Talang Padang Village include: (a) high intensity of digital media use through smartphones and social media, (b) online activities such as studying, discussing and communicating, (c) quickly adapting to fairly good technology, (d) thinking quickly in responding to information, (e) thinking critically in assessing and comparing information, and (f) wanting to be practical. Meanwhile, the socio-religious behavior of Generation Z still shows religious values ​​through: (a) carrying out worship which includes 1. praying behavior, 2. Behavior of saying greetings and 3. Behavior of giving alms, 4. behavior of fasting; (b) participation in activities to commemorate Islamic holidays (PHBI); and (c) maintaining good relations and morals in the social life of the community.